BUDAYA KERJA DAN KOMITMEN KERJA TERHADAP KEPUASAN KERJA PEGAWAI SUKU DINAS SUMBER DAYA AIR JAKARTA UTARA - Tita Amelia; Arief Syah Safrianto (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
This research aims to determine the influence of work culture and work commitment on job satisfaction of employees at the Water Resources Agency of the North Jakarta City Administration. The research method uses quantitative methods. The results of this research show that work culture and work commitment have a positive and significant effect on employee job satisfaction, both partially and simultaneously.